Dietary zinc deficiency or supplementation during gestation increases breast cancer susceptibility in adult female mice offspring following a J-shaped pattern and through distinct mechanisms. (December 2019) - da Cruz, Raquel Santana; Andrade, Fabia de Oliveira; Carioni, Vivian Montes de Oca; Rosim, Mariana Papaléo; Miranda, Mayara Lilian Paulino; Fontelles, Camile Castilho; de Oliveira, Pedro Vitoriano; Barbisan, Luis Fernando; Castro, Inar Alves; Ong, Thomas Prates
Abstract: Zinc is required for fetal development and is involved in key processes associated with breast carcinogenesis. We evaluated whether maternal zinc deficiency or supplementation during gestation influences female offspring susceptibility to breast cancer in adulthood. C57BL/6 mice consumed during gestation control (30 p.p.m. zinc), zinc-deficient (8 p.p.m) or zinc-supplemented (45 p.p.m.) diets. Maternal zinc supplementation increased in female mice offspring the incidence of chemically-induced mammary adenocarcinomas that were heavier, compared to control group. This was accompanied by a decreased number of terminal end buds, increased cell proliferation and apoptosis, and increased tumor suppressors p21, p53 and Rassf1, Zfp382 and Stat3 expression in mammary glands, as well as increased zinc status. Although maternal zinc deficiency did not alter the incidence of these lesions, it also induced heavier mammary adenocarcinomas, compared to control group. These effects were accompanied by a decreased number of terminal end buds, increased proto-oncogenes c-Myc and Lmo4 expression and H3K9Me3 and H4K20Me3 epigenetic marks in mammary glands of offspring, and decreased zinc status and increased levels of oxidative marker malondialdehyde. The data suggest that both maternal zinc deficiency and supplementation during gestation programmed increased breast cancer susceptibility in adult mice offspring following a J-shaped pattern through distinct mechanisms. Highlights: Gestational Zn supplementation programmed breast cancer in female mice offspring. Gestational Zn deficiency programmed breast cancer in female mice offspring. Zn supplementation altered mammary cell growth and tumor suppressors expression. Zn deficiency altered mammary proto-oncogenes expression and histone marks. Zinc breast cancer programming follows a J-shaped pattern and distinct mechanisms.